Structural and Kinetic Characterization of Hyperthermophilic NADH-Dependent Persulfide Reductase from Archaeoglobus fulgidus. (10th March 2021) - Shabdar, Sherwin; Anaclet, Bukuru; Castineiras, Ana Garcia; Desir, Neyissa; Choe, Nicholas; Crane, Edward J.; Sazinsky, Matthew H.
Abstract : NADH-dependent persulfide reductase (Npsr) has been proposed to facilitate dissimilatory sulfur respiration by reducing persulfide or sulfane sulfur-containing substrates to H2 S. The presence of this gene in the sulfate and thiosulfate-reducing Archaeoglobus fulgidus DSM 4304 and other hyperthermophilic Archaeoglobales appears anomalous, as A. fulgidus is unable to respire S 0 and grow in the presence of elemental sulfur. To assess the role of Npsr in the sulfur metabolism of A. fulgidus DSM 4304, the Npsr from A. fulgidus was characterized. AfNpsr is specific for persulfide and polysulfide as substrates in the oxidative half-reaction, exhibiting k cat / K m on the order of 10 4 M -1 s -1, which is similar to the kinetic parameters observed for hyperthermophilic CoA persulfide reductases. In contrast to the bacterial Npsr, AfNpsr exhibits low disulfide reductase activity with DTNB; however, similar to the bacterial enzymes, it does not show detectable activity with CoA-disulfide, oxidized glutathione, or cystine. The 3.1 Å X-ray structure of AfNpsr reveals access to the tightly bound catalytic CoA, and the active site Cys 42 is restricted by a flexible loop (residues 60-66) that is not seen in the bacterial homologs from Shewanella loihica PV-4 and Bacillus anthracis . Unlike the bacterial enzymes, AfNpsr exhibits NADH oxidase activity and also shows no detectable activity with NADPH. Models suggest steric and electrostatic repulsions of the NADPH 2 ′ -phosphate account for the strong preference for NADH. The presence of Npsr in the nonsulfur-reducing A. fulgidus suggests that the enzyme may offer some protection against S 0 or serve in another metabolic role that has yet to be identified.